2020
DOI: 10.1186/s12884-020-2795-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and determinants of an optimal ANC visit among pregnant women in Ethiopia: further analysis of 2016 Ethiopia demographic health survey

Abstract: Background: Antenatal care (ANC) is essential to improve maternal and newborn health and wellbeing. Antenatal care coverage is improving in Africa since over two-thirds of pregnant women have at least one ANC contact. However, to realize the complete life-saving potential that ANC guarantees for mothers and babies, at least four visits providing essential evidence-based interventions are required.. Therefore, this study was conducted to identify determinants of an optimal ANC visit and its spatial distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
4
16
0
Order By: Relevance
“…The finding showed that in the current study pregnant women in the middle, richer, and richest households were more likely to have frequent ANC visits compare to those in the poorest household. This result is similar to the studies conducted in other countries including Ethiopia [9,13,25,28,31]. This is maybe because of the easy to afford the transportation and health service fee the pregnant mothers who got the service they want, and most of the time mothers from the above-mentioned wealth quintile having access to get an education and different mass media system.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The finding showed that in the current study pregnant women in the middle, richer, and richest households were more likely to have frequent ANC visits compare to those in the poorest household. This result is similar to the studies conducted in other countries including Ethiopia [9,13,25,28,31]. This is maybe because of the easy to afford the transportation and health service fee the pregnant mothers who got the service they want, and most of the time mothers from the above-mentioned wealth quintile having access to get an education and different mass media system.…”
Section: Discussionsupporting
confidence: 86%
“…Maternal educational status had a significant effect on the number of antenatal care visits in developing countries. This result is supported by most of the studies related to ANC service conducted somewhere [2,9,11,13,21,25,28]. This could be because educated mothers were more concerned with the outcome of their pregnancy and pregnancy complications, and they were close to seeking health care services.…”
Section: Discussionsupporting
confidence: 53%
“…There is strong evidence suggesting that religion, level of education, occupation, distance from the health facility, residence, country, mass media, maternal age, and wealth index were associated with ANC utilization. [7][8][9][10][11][12][13][14] From the previous, many sociocultural factors were associated with late ANC booking. 15,16 Among the factors likely to be critical in health promotional activities and health services uptake is educational attainment.…”
Section: Introductionmentioning
confidence: 89%
“…For instance, in Ethiopia, a relatively higher utilization was found in Addis Ababa [ 31 - 37 ], Dire Dawa [ 31 , 34 - 37 ], Tigray [ 31 , 33 - 39 ], and Harari [ 31 , 33 , 35 , 36 ]. A relatively low utilization was found in regions of Somali [ 31 , 33 , 34 , 36 , 37 , 39 ], Afar [ 31 , 33 - 35 , 37 ], Oromia [ 32 , 33 , 35 , 36 , 39 ], most of Amhara [ 33 - 35 , 37 , 40 ], Gambela [ 32 , 33 , 37 , 39 ], Benishangul Gumuz [ 34 , 35 ], and parts of Southern Nations Nationalities and Peoples Region [ 32 , 34 - 36 , 39 , 40 ]. Similarly, a significant north-south divide in the likelihood of maternal health care utilization was reported in Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…Inequality in maternal health care utilization was also identified at a national level. For instance, in Ethiopia, a relatively higher utilization was found in Addis Ababa [31][32][33][34][35][36][37], Dire Dawa [31,[34][35][36][37], Tigray [31,[33][34][35][36][37][38][39], and Harari [31,33,35,36]. A relatively low utilization was found in regions of Somali [31,33,34,36,37,39], Afar [31,[33][34][35]37], Oromia [32,33,35,36,39], most of Amhara [33][34][35]37,40], Gambela [32,33,37,39], Benishangul Gumuz…”
Section: Identifying Inequalities In Maternal Health Care Utilizationmentioning
confidence: 99%